High-Resolution Methane Mapping With the EnMAP Satellite Imaging Spectroscopy Mission - Roger, Javier; Irakulis-Loitxate, Itziar; Valverde, Adriana; Gorroño, Javier; Chabrillat, Sabine; Brell, Maximilian; Guanter, Luis (IEEE transactions on geoscience and remote sensing, 2024)
Methane (CH4) mitigation from anthropogenic sources such as in the production and transport of fossil fuels has been found as one of the most promising strategies to curb global warming in the near future. Satellite-based imaging spectrometers have demonstrated to be well-suited to detect and quantify these emissions at high spatial resolution, which allows the attribution of plumes to sources. The PRecursore IperSpettrale della Missione Applicativa (PRISMA) satellite mission (ASI, Italy) has been successfully used for this application, and the recently launched Environmental Mapping and Analysis Program (EnMAP) mission (DLR/GFZ, Potsdam, Germany) presents similar spatial and spectral characteristics (30-m spatial resolution, 30-km swath, about 8-nm spectral sampling at 2300 nm). In this work, we investigate the potential and limitations of EnMAP for CH4 remote sensing, using PRISMA as a benchmark to deduce its added value. We analyze the spectral and radiometric performance of EnMAP in the 2300-nm region used for CH4 retrievals acquired using the matched-filter method. Our results show that in arid areas, EnMAP spectral resolution is about 2.7 nm finer and the signal-to-noise ratio values are approximately twice as large, which leads to an improvement in retrieval performance. Several EnMAP examples of plumes from different sources around the world with flux rate values ranging from 1 to 20 t/h are illustrated. We show plumes from sectors such as onshore oil and gas (O&G) and coal mining, but also from more challenging sectors such as landfills and offshore O&G. We detect two plumes in a close-to-sunglint configuration dataset with unprecedented flux rates of about 1 t/h, which suggests that the detection limit in offshore areas can be considerably lower under favorable conditions.